The Correlation between Lipid Profile and Smoking - Mohammed Jasim Qasim1 , Israa Q. Falih2, Faten Khudhair Al_Husaini3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The objectives were to find out the alterations in serum lipid status among adult male smokers and non smokers in Maysan Province, south of Iraq, as well as to evaluate the relationship between the heaviness of smoking and dyslipidemia in smoker subjects. A comparative study was achieved on 160 men with aged 30-63 years which were grouped to smokers and nonsmokers, among them 120 individuals were smokers and the other 40 were nonsmokers. According to the intensity of smoking, the smoker group is divided again into three subgroups: mild (A), moderate (B), and heavy (C) smokers. The concentrations of total cholesterol (TC), high density lipoprotein-c (HDL-c), triglycerides (TG), low density lipoprotein-c (LDL-c) and very low density lipoprotein-c (LDL-c) were measured and calculated. The results revealed that concentrations of serum lipid profiles in smokers were significantly higher than that of nonsmokers except in case of high density lipoprotein-c which was significantly reduced among smokers. In addition to that the lipid profile had a significant correlation with the cigarette numbers of that smoked daily; the mean values of all lipid fractions except HDL-c were noticeably increased from group A to group C, while they were decreased in the case of HDL-C. There were significantly different between nonsmokers and different groups of the smoker, the values of TC of groups A, B, and group C were (178.6, 181.7, and 183.5) mg/dl respectively. According to similar arrangement of above smoker groups, the mean values of TG were (238.4, 245.2, and 248.7) mg/dl. In case of HDL- c, they were (31.5, 28.4, and 26.8) mg/dl. Among LDL-c level, they were (194.8, 203.8, and 204.9) mg/dl. In VLDL- c level, they were (47.7, 48.2, and 50.5) mg/dl. The findings of the study showed that smokers (especially heavy smokers) are at much greater risk of initiating atherosclerotic plaques and various heart diseases than non-smokers.